ETIKA DAN ESTETIKA MEUDIKEE ANGGOK DI DAYAH DARUL HUDA DESA BAYI KECAMATAN TANAH LUAS LHOKSUKON KABUPATEN ACEH UTARA - Erna Fitriyawati; Iskandar Muda (Universitas Negeri Medan, 2018)
ABSTRACT This study discusses the Value of Ethics and Aesthetics Meudikee Anggok In Dayah Darul Huda Bayi Village District Lhoksukon District Luas Aceh. Aims to describe Ethical and Esthetic Value of Meudikee Anggok In Dayah Darul Huda Bayi Village, Lhoksukon Sub-district, Lhokukon District, Aceh. The theory used in this study is the ethical theory of K. Bertens According to K. Bertens The ethical theory according to K. Bertens (1993: 53) that ethics is the conscience (inner life), how to be ethical and good that actually arise from self awareness. Based on the theory of K. Bertens concluded that every human being has experience of the conscience and that experience is the most obvious encounter with morality as a reality, it is difficult to show another experience that is so frankly the ethical dimension of our lives. Hence the experience of the conscience is an appropriate entry point about ethics. Time in use in this study is during (two months), ie from July to September. The location of this research was conducted in Bayi Village, North Aceh District. The population in this study are artists who know about Meudikee Anggok dance, and the sample is Aneuk Dikee (son of Zikir). The research data analysis used is descriptive qualitative, data collecting technique done by obsevasi, literature study, interview, and documentation. Based on the data collected, it can be seen that Meudikee Anggok has been known for a long time. The number of boys who performed Meudikee Anggok at the beginning of choreographer formation was 16 Aneuk Dikee and 4 syeh (radad). Meudikee anggok has ethical values contained in the ethics of movement 1. Respect 2. Saleum. 6. Noble Prophets and 7. Prayers. Aesthetic value that can be observed every movement at 3. Istigfar, 4. Salawat prophets and 5. Qasas. Keywords: Meudikee Anggok Di Dayah darul Huda Deswa Bayi Kecamatan Luas Lhoksukon Kabupaten Aceh Utara,Ethics and Aesthetics.